2017
DOI: 10.1039/c6ra25135h
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stimuli-responsive self-repairing waterbased superhydrophobic coatings

Abstract: Superhydrophobic coatings have received great attention over the past decades because of their specific performances, but most of them may lose their superhydrophobicity under harsh conditions especially in outdoor applications. In this paper, UV and pH dual stimuli-responsive self-repairing waterbased superhydrophobic coatings were prepared based on TiO 2 with photocatalysis and pH-responsive microcapsules, which were durable against UV irradiation and chemically stable in contact with alkaline or acidic aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The N 1s peak was only observed at 399.1 eV (Figure 6d), which was due to the deprotonation of PDMAEMA. 3032 In terms of atomic content, the N atom content of the modified paper without the acid/alkali treatment was 0.11%. After the acid treatment, the N atom content on the surface of the paper increased to 0.55%.…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s peak was only observed at 399.1 eV (Figure 6d), which was due to the deprotonation of PDMAEMA. 3032 In terms of atomic content, the N atom content of the modified paper without the acid/alkali treatment was 0.11%. After the acid treatment, the N atom content on the surface of the paper increased to 0.55%.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained superhydrophobic surface demonstrated durable anti‐icing properties even after 60 cycles of icing‐melting processes (Figure 16d–f), indicating a superior long lifetime than other reported anti‐icing coatings. [ 53 ]…”
Section: Applications Of Self‐healing Superhydrophobic Surfacesmentioning
confidence: 99%
“…FAS-TiO 2 /PDMS superhydrophobic sandpaper surface (FTPSS) exhibit excellent self-cleaning and anti-snow/anti-icing performance even after 50 abrasion cycles with sandpaper and prevented snow and ice from adhering to the substrate (Qing et al 2019). K. Chen et al have reported the UV and pH dual stimuli-responsive self-repairing water-based superhydrophobic TiO 2 coatings which were prepared by spray process using perfluorooctyltriethoxysilane (FAS13) with WCA of 155.3 (Chen et al 2017). S. Liu et al have fabricated polydopamine and TiO 2 coatings on sand surfaces and subsequent hydrophobic modification (WCA~153 ) with low surface energy material (Liu et al 2019).…”
Section: Surface Functionalizationmentioning
confidence: 99%